Cytokine regulation of T-cell function: potential for therapeutic intervention. - Powrie, F; Coffman, R (1993)
CD4+ T cells, via the cytokines that they produce, play a pivotal role in the induction and regulation of cell-mediated and humoral immunity. Recently it has become clear that the CD4+ T-cell population is heterogeneous and that distinct CD4+ T-cell subsets, defined by their cytokine repertoire, regulate cell-mediated and humoral immune responses. Protective responses to pathogens are dependent on activation of the appropriate TH subset accompanied by its characteristic set of immune effector functions. Evidence to date suggests that the cytokines produced by the TH cells themselves are important regulators of TH subset activation and differentiation. Fiona Powrie and Robert Coffman discuss how manipulation of the levels of these cytokines can be used to alter the balance of TH-cell subsets and illustrate some clinical situations where this may be beneficial.